Decarbonization process and productivity convergence: a global analysis of carbon total factor productivity - Jing Liu; Jianing Zhang; Dengfeng Cui (Carbon Balance and Management)
Abstract Background In the context of mitigating global warming and promoting sustainable development, the scientific and effective assessment of the global carbon total factor productivity (CTFP) is essential for slowing global warming and fostering green transformation and coordinated development at both the global and regional levels. Methods This study constructs a CTFP evaluation index system and, for the first time, employs the SBM-DDF-GML productivity index model to measure the CTFP of 137 countries worldwide from 1991 to 2019. This model combines a directional distance function with the global Malmquist–Luenberger index to achieve precision in efficiency measurement and intertemporal comparability. It effectively resolves the problems of estimation bias and time dimension inconsistency caused by the radial assumption in traditional radial models. The spatial characteristics, regional disparities, and sources of these disparities in the CTFP are examined using ArcGIS and the Dagum Gini coefficient method. The σ-convergence and β-convergence models are used to investigate the influencing factors and convergence characteristics of the CTFP. Results The findings reveal that (1) the global CTFP exhibited an overall upward trend with fluctuations over the sample period, with technological progress being the primary driving force. (2) There are significant gradient disparities in the global CTFP, primarily stemming from supervariable density, followed by intraregional and interregional differences, and these disparities are expanding. (3) While there is no evident σ-convergence in the global CTFP and CTFP of the four major regions, there are significant absolute and conditional β-convergence trends. Conclusion Based on the research results, this paper proposes specific strategies to promote the global development of CTFP. These include strengthening technology R&D to improve CTFP, encouraging regional convergence to reduce development disparities, and enhancing the dynamic monitoring and evaluation system to foster growth and equity. This study provides empirical support and a decision-making basis for the coordinated development of the global economy and environment, contributing to advancing global green, low-carbon, and sustainable development.